Melanoma addiction to the long non-coding RNA SAMMSON - Leucci, Eleonora; Vendramin, Roberto; Spinazzi, Marco; Laurette, Patrick; Fiers, Mark; Wouters, Jasper; Radaelli, Enrico; Eyckerman, Sven; Leonelli, Carina; Vanderheyden, Katrien; Rogiers, Aljosja; Hermans, Els; et al. (Nature (London), 2016)
A known oncogene, MITF , resides in a region of chromosome 3 that is amplified in melanomas and associated with poor prognosis; now, a long non-coding RNA gene, SAMMSON , is shown to also lie in this region, to also act as a melanoma-specific survival oncogene, and to be a promising therapeutic target for anti-melanoma therapy. An oncogenic non-coding RNA The known oncogene MITF is found in the 3p13–3p14 region of chromosome 3 that is amplified in melanomas and associated with poor prognosis. This study shows that a long non-coding RNA, SAMMSON , also lies in this region and is co-gained with MITF . SAMMSON interacts with p32 and thereby affects mitochondrial function in a pro-oncogenic manner. SAMMSON depletion sensitizes melanoma cells to MAPK-targeting therapeutics in vivo and in patient-derived xenograft models. These results point to SAMMSON as a potentially useful biomarker for malignancy and as an anti-melanoma therapeutic target. Focal amplifications of chromosome 3p13–3p14 occur in about 10% of melanomas and are associated with a poor prognosis. The melanoma-specific oncogene MITF resides at the epicentre of this amplicon 1 . However, whether other loci present in this amplicon also contribute to melanomagenesis is unknown. Here we show that the recently annotated long non-coding RNA (lncRNA) gene SAMMSON is consistently co-gained with MITF . In addition, SAMMSON is a target of the lineage-specific transcription factor SOX10 and its expression is detectable in more than 90% of human melanomas. Whereas exogenous SAMMSON increases the clonogenic potential in trans , SAMMSON knockdown drastically decreases the viability of melanoma cells irrespective of their transcriptional cell state and BRAF , NRAS or TP53 mutational status. Moreover, SAMMSON targeting sensitizes melanoma to MAPK-targeting therapeutics both in vitro and in patient-derived xenograft models. Mechanistically, SAMMSON interacts with p32, a master regulator of mitochondrial homeostasis and metabolism, to increase its mitochondrial targeting and pro-oncogenic function. Our results indicate that silencing of the lineage addiction oncogene SAMMSON disrupts vital mitochondrial functions in a cancer-cell-specific manner; this silencing is therefore expected to deliver highly effective and tissue-restricted anti-melanoma therapeutic responses.